US open skies agreements and unlevel playing fields. (January 2019) - Morrison, William G.; de Wit, Jaap
Abstract: We examine the relationship between 'Open Skies' agreements (OSAs) signed between the USA and various countries or regions and the existence of subsidies and other forms of protection that advantage one nation's airlines over those of co-signatories to an OSA. We argue that under an oligopoly market structure, strategic competition brought about by OSAs creates incentives to subsidize and/or protect domestic airlines. Such incentives are maintained or amplified by political lobbying efforts that bias civil aviation policies towards producer interests over wider measures of economic welfare. We report on financial aid and policies which have advantaged US airlines during the OSA period and which suggest that unlevel playing fields have been made more unlevel during the era of OSAs. Highlights: 'Open skies' agreements can lead to strategic competition and subsidies. US jurisdictions have unlevelled the playing field during the Open Skies era. US airlines took advantage of federal aid in debt restructuring. US airlines benefited from market foreclosure and surplus enhancing policies.